2021
DOI: 10.1038/s41467-020-20479-4
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic glucose metabolism regulates the redox circadian clockwork in human red blood cells

Abstract: Circadian clocks coordinate mammalian behavior and physiology enabling organisms to anticipate 24-hour cycles. Transcription-translation feedback loops are thought to drive these clocks in most of mammalian cells. However, red blood cells (RBCs), which do not contain a nucleus, and cannot perform transcription or translation, nonetheless exhibit circadian redox rhythms. Here we show human RBCs display circadian regulation of glucose metabolism, which is required to sustain daily redox oscillations. We found da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 62 publications
6
53
0
Order By: Relevance
“…Several independent lines of evidence demonstrate molecular and metabolic oscillations in the absence of Bmal1 (7,8) or an alternative clock knockout model [Cryptochrome-deficient mice (9)], supporting our observations. To establish that transcriptome-level oscillations observed in Bmal1 -/cells are "noise" rather than true circadian rhythmicity, the authors could perform identical experiments within an environment that they think is completely devoid of external cues to verify that there are absolutely no 24-hour molecular oscillations in cultured Bmal1 -/cells under constant conditions.…”
supporting
confidence: 88%
“…Several independent lines of evidence demonstrate molecular and metabolic oscillations in the absence of Bmal1 (7,8) or an alternative clock knockout model [Cryptochrome-deficient mice (9)], supporting our observations. To establish that transcriptome-level oscillations observed in Bmal1 -/cells are "noise" rather than true circadian rhythmicity, the authors could perform identical experiments within an environment that they think is completely devoid of external cues to verify that there are absolutely no 24-hour molecular oscillations in cultured Bmal1 -/cells under constant conditions.…”
supporting
confidence: 88%
“…2, F and G). Furthermore, Bmal1 -/skin fibroblasts show circadian metabolic flux oscillations under constant conditions (15). These data provide further evidence of self-sustained circadian oscillations in Bmal1 -/cells and tissues under constant conditions.…”
supporting
confidence: 60%
“…nucleus, mitochondria, endoplasmic reticulum etc.) [ 8 , 9 ] and catalyzes the formation of N-terminal pyroglutamate (pGlu) by converting glutamate/glutamine to pGlu residue similar as the secretory isoenzyme Glutaminyl cyclases (QC) [ 1 , 10 , 11 ]. Prior researches have indicated that isoQC is the critical regulator of pGlu modification of CD47 N-terminal peptide and resultantly affects the interaction between CD47 and SIRPα [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%